Tumor-Derived Extracellular Vesicles Induce Abnormal Angiogenesis via TRPV4 Downregulation and Subsequent Activation of YAP and VEGFR2 - Guarino, Brianna; Katari, Venkatesh; Adapala, Ravi; Bhavnani, Neha; Dougherty, Julie; Khan, Mahmood; Paruchuri, Sailaja; Thodeti, Charles (Frontiers in Bioengineering and Biotechnology, 2021)
Tumor angiogenesis is initiated and maintained by the tumor microenvironment through secretion of autocrine and paracrine factors, including extracellular vesicles (EVs). Although tumor-derived EVs (t-EVs) have been implicated in tumor angiogenesis, growth and metastasis, most studies on t-EVs are focused on proangiogenic miRNAs and growth factors. We have recently demonstrated that conditioned media from human lung tumor cells (A549) downregulate TRPV4 channels and transform normal endothelial cells to a tumor endothelial cell-like phenotype and induce abnormal angiogenesis in vitro, via t-EVs. However, the underlying molecular mechanism of t-EVs on endothelial cell phenotypic transition and abnormal angiogenesis in vivo remains unknown. Here, we demonstrate that t-EVs downregulate TRPV4 expression post-translationally and induce abnormal angiogenesis by activating Rho/Rho kinase/YAP/VEGFR2 pathways. Further, we demonstrate that t-EVs induce abnormal vessel formation in subcutaneously implanted Matrigel plugs in vivo (independent of tumors), which are characterized by increased VEGFR2 expression and reduced pericyte coverage. Taken together, our findings demonstrate that t-EVs induce abnormal angiogenesis via TRPV4 downregulation-mediated activation of Rho/Rho kinase/YAP/VEGFR2 pathways and suggest t-EVs and TRPV4 as novel targets for vascular normalization and cancer therapy.